2020
DOI: 10.1177/0308022620950993
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of a combined model of online interventions for adults with cancer-related cognitive impairment

Abstract: Introduction The purpose of this study was to test the feasibility of a telehealth intervention combining computerised cognitive training and occupation-based treatment among adult cancer survivors experiencing cancer-related cognitive impairment. Method This was a single-arm study including six cancer survivors with cancer-related cognitive impairment. Participants completed the computerised retraining and functional treatment intervention consisting of 10 hours of computerised cognitive training (BrainHQ) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The group results, as well as the individual results, are in line with previous traditional face-to-face CO-OP studies with this population [ 27 , 29 , 31 , 33 , 34 , 74 , 75 , 76 ]. In addition, our preliminary results corroborated previous CO-OP telerehabilitation feasibility studies that reported improved daily function among adults in the chronic phase after ABI [ 32 , 39 ] and individuals with other health conditions, including cancer survivors with cognitive decline [ 36 ], older adults with subjective cognitive complaints [ 35 ], and adolescents with myelomeningocele [ 37 ]. Moreover, this is the first pilot study to evaluate the benefits of tele-CO-OP in comparison to a control group, thus extending the previous quasi-experimental tele-CO-OP findings.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The group results, as well as the individual results, are in line with previous traditional face-to-face CO-OP studies with this population [ 27 , 29 , 31 , 33 , 34 , 74 , 75 , 76 ]. In addition, our preliminary results corroborated previous CO-OP telerehabilitation feasibility studies that reported improved daily function among adults in the chronic phase after ABI [ 32 , 39 ] and individuals with other health conditions, including cancer survivors with cognitive decline [ 36 ], older adults with subjective cognitive complaints [ 35 ], and adolescents with myelomeningocele [ 37 ]. Moreover, this is the first pilot study to evaluate the benefits of tele-CO-OP in comparison to a control group, thus extending the previous quasi-experimental tele-CO-OP findings.…”
Section: Discussionsupporting
confidence: 86%
“…The use of the CO-OP remotely (Tele-CO-OP) enables the application of the intervention in an accessible manner in the home environment. The feasibility and the potential long-term benefits of the tele-CO-OP were demonstrated in a few small pilot studies among patients with various chronic health conditions [ 35 , 36 , 37 ]. Tele-CO-OP meets the definition of a complex intervention; therefore, the development and evaluation process can be based on the Medical Research Council (MRC) guidelines [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result supports a recent study which found that developing and maintaining a therapeutic relationship is feasible also in a remote mode of delivery. 8 …”
Section: Discussionmentioning
confidence: 99%
“… 4 OT delivered remotely has proven to be highly acceptable and effective for individuals with a variety of health conditions across their life-span. 5 Efficacy had also been established in multiple studies analyzing interventions for varying populations such as children with autism, 6 adolescents with myelomeningocele, 7 adults cancer-survivors, 8 , 9 and people with acquired brain injury. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation